A inserção de educação ambiental na pesquisa e na extensão - Barbosa, Aldovano Dantas [UNESP]; Vale, Bianca Barbosa do [UNESP]; Cardoso, Denise [UNESP]; Santos, Élica [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Text is to support work in conjunction plural that moves a flap time, particularly from 2012 to 2015; in an urban world of the suburbs of the city of Franca, State of São Paulo; inside the school and outside the universe, that is, in the routine of inserting quarters of state schools in kindergarten, primary and secondary. Under the atmosphere of the early century. XXI and the taste of the relentless movement of synergy between principles are for a (re) epistemological order, the work done so far open the range and integrate local contexts planetary. These writings have for basting, the onemultiple of the subjects involved in a complex of thinking and doing environmental education way. Talk time / space distraught weaving / unravel / (re) sew theoretical research, Course and everyday to study circles (Paulo Freire) and extension activities on the environment and environmental education for sustainable societies. The article has an essayist character. The theoretical framework, method, methodology and praxis Group browse a critical reflection and self-criticism movement Complex Thought.

O texto apresentado tem por suporte um trabalho conjugado no plural que se movimenta num retalho do tempo, em particular de 2012 a 2015; num mundo urbano dos bairros periféricos da cidade de Franca, Estado de São Paulo; no interior do universo escolar e fora dele, isto é, no cotidiano dos bairros de inserção de escolas estaduais de ensino infantil, fundamental e médio. Sob a atmosfera do início do séc. XXI e ao sabor do movimento incansável de sinergia entre princípios que estão para uma (re) ordenação epistemológica, os trabalhos realizados até o momento abrem o leque e integram contextos locais aos planetários. Esses escritos contam em alinhavos, do uno-múltiplo dos sujeitos envolvidos por um jeito complexo de pensar e fazer educação ambiental. Falam do tempo/espaço desassossegado de tecer/descosturar/(re)costurar pesquisas teóricas, De Campo e do cotidiano aos círculos de estudos (Paulo Freire) e às atividades de extensão em meio ambiente e educação ambiental para sociedades sustentáveis. O artigo tem um caráter ensaísta. O aporte teórico, de método, de metodologia e de práxis do Grupo navega num movimento de reflexão crítica e autocrítica do Pensamento Complexo.
Keywords: Environmental education; Research; Complex thought; Educação ambiental; Pesquisa; Pensamento complexo